Centrifugálisból centripetális? : Tito kísérlete a koszovói kérdés rendezésére : 1945-1980 - Gulyás, László (Közép-Európai Közlemények, 2008)
In one of his most important book, titled „The dissolution of Habsburg monarchy” Oszkar Jaszi distinguished centrifugal and centripetal powers from point of view of multinational state. In this study I show that Albanian minority of Kosovo how and why hesitated between the role of centrifugal and centripetal power within the Tito-leaded Yugoslav state, which was multinational similarity Habsburg monarchy.